2003
DOI: 10.1007/s00213-003-1392-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, neuroendocrine and neurochemical effects of the imidazoline I2 receptor selective ligand BU224 in naive rats and rats exposed to the stress of the forced swim test

Abstract: The selective I(2) receptor ligand BU224 reduces immobility of rats in the FST, indicative of antidepressant-like activity. This effect is accompanied by alterations in HPA axis and central monoaminergic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 62 publications
2
27
1
Order By: Relevance
“…Water depth was 40 cm, and temperature was maintained at 23 Ϯ 1°C. Stress exposure was always commenced at 9:00 A.M., when the plasma corticosterone levels are low (Finn et al, 2003, Krugers et al, 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Water depth was 40 cm, and temperature was maintained at 23 Ϯ 1°C. Stress exposure was always commenced at 9:00 A.M., when the plasma corticosterone levels are low (Finn et al, 2003, Krugers et al, 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, I 2 sites have been linked to several central nervous system disorders for which changes in the binding density have been observed in postmortem brain tissue. These include depression (5,6), addiction (7), glial tumor (8)(9)(10), and neurodegenerative disorders such as Alzheimer's disease (11) and Huntington's chorea (12). An in vivo imaging probe to study I 2 sites in living tissue would therefore prove invaluable in further delineating the precise physiologic role of these binding sites in healthy and disease states.…”
mentioning
confidence: 99%
“…Preclinical studies have shown that harmane exhibits anxiolytic and anti-depressant properties [120], which was also projected by I 2 -BS ligands [11,70,121]. In restraint-stressed rats, harmane and BU224 treatment elevated Fos expression in distinct brain regions in a comparable manner; emphasizing the overlap of these molecules for the same target site [12].…”
Section: Harmane -The Endogenous Ligand At Imidazoline Binding Sites?mentioning
confidence: 99%
“…In addition, the immunoreactivity of the I 1 -BS protein candidate IRAS, as well as the proposed 29/30 kD I 2 -BS protein, were also notably changed in platelets and brains of depressed suicide victims in comparison to healthy subjects [66,67]. In preclinical studies, selective I 2 -BS compounds such as 2-BFI and BU224 exhibited antidepressant activity by regulating central monoamine levels [68,69] and increasing mobility time in the Porsolt forced swim paradigm [11,70,71]. Behaviour analyses showed that agmatine along with I-BS ligands (2-BFI, moxonidine and clonidine) mediated the antidepressant like effects of selective serotonin reuptake inhibitors (SSRIs).…”
Section: Imidazoleacetic Acid Ribotide Agmatinementioning
confidence: 99%
See 1 more Smart Citation